Comparative study of the theory of constraints and the philosophy of just-in-time - Plantullo, Vicente Lentini; Imoniana, Joshua Onome; Nohara, Jouliana Jordan (Anais do Congresso Brasileiro de Custos - ABC)
The Objective of this paper is to compare and contrast two philosophies of managerial science namely Just-in-Time and the Theory of Constraints. The research was produced based on literature review using inductive approach towards analytical and interpretative procedures. To execute the research procedures, firstly, we analyze the fundamentals of the mentioned philosophies. Secondly, we emphasize earnings versus the costs behaviors, hitherto highlighting the surrounding concepts and their practical application, thus retrieving the relationship among lung, drum and string, the words used by Eliyahu M. Goldratt, the father of the Theory of Constraints. Finally, the factors that enhance maximization of the throughput period in the manufacturing processes such as production capacity, batch sizes, timings, accuracy, planning & control, flexibility and costs were compared. Results reveal that there is a clear need for a change in the manufacturing methodologies so that firms could be competitive, therefore, in order to attain objectives in a competitive environment one could adopt the convincing JIT or TOC philosophies.